Meningkatkan Hasil Belajar dengan Menggunakan Model Pembelajaran Problem Based Learning (PBL) pada Materi Peluang Siswa Kelas VIII SMPK St. Theresia Kupang - Mega Nirmala Mboa; Timoteus Ajito (Departement of Mathematics Education, 2024)
factors, which involve the development of learning programs and delivery strategies or learning processes. What is no less important is how teachers design the teaching and learning process and carry out innovations in the learning process such as the utilization and use of media, teaching materials, and appropriate learning models that are adapted to the conditions of students so that learning objectives and student learning outcomes can be achieved in accordance with hopes to be achieved and get maximum results. This research aims to find out, 1) How the Problem Based Learning (PBL) learning model is applied to Opportunity Material 2) What are the Student Learning Results Using the Problem Based Learning (PBL) Learning Model. This research uses a qualitative approach where data is obtained using Miles Matthew analysis. B and Huberman Michael, which consists of three stages, namely data reduction, data presentation, and ending with drawing conclusions. The research results show that there is an increase in student learning outcomes by using the Problem Based Learning (PBL) learning model on Opportunity Material.